2009
DOI: 10.1111/j.1467-7652.2009.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The pleiotropic effects of thebargene and glufosinate on theArabidopsistranscriptome

Abstract: SummaryThe Arabidopsis transcriptome was studied using the Affymetrix Arabidopsis ATH1 GeneChip in wild-type plants and glufosinate-tolerant transgenic plants expressing the bialaphos resistance ( bar ) gene. Pleiotropic effects were specifically generated in the transcriptomes of transgenic plants by both the bar gene and glufosinate treatments. In the absence of glufosinate, four genes were differentially expressed in the transgenic lines and another 80 genes were differentially expressed in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 73 publications
1
7
0
1
Order By: Relevance
“…Genetic transformation can produce unintended pleiotropic effects on occasion (Yabor et al, 2006;Abdeen and Miki, 2009) that negatively affect plant phenotype. In tobacco (Nicotiana tabacum), for example, stilbene overexpression led to male sterility (Fischer et al, 1997;Hö fig et al, 2006), probably due to shortages of substrates for flavonoid and sporopollenin production.…”
Section: Genetic Transformation Of Spruce With Pasts Provided New Insmentioning
confidence: 99%
“…Genetic transformation can produce unintended pleiotropic effects on occasion (Yabor et al, 2006;Abdeen and Miki, 2009) that negatively affect plant phenotype. In tobacco (Nicotiana tabacum), for example, stilbene overexpression led to male sterility (Fischer et al, 1997;Hö fig et al, 2006), probably due to shortages of substrates for flavonoid and sporopollenin production.…”
Section: Genetic Transformation Of Spruce With Pasts Provided New Insmentioning
confidence: 99%
“…Furthermore, the mating competence of plot B decreased as the distance to the recipients increased, as expected based on the behavior of bees in citrus orchards [12].…”
Section: Discussionsupporting
confidence: 78%
“…Cross-pollination in citrus is accomplished by insects, and honeybees are the most successful pollinators [12]. In insect-pollinated plants, pollen dispersal is generally the main component of gene flow [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, cold treatment triggered changes in only 10 protein spots. In another study, Abdeen and Miki (2009) found only four genes differentially expressed in transgenic lines expressing bar.…”
mentioning
confidence: 99%